Why your DAG should probably incorporate sampling and measurement processes - Robin J Boyd; Rob Cooke; Gary D Powney; Oliver L Pescott (Current Opinion in Insect Science, 2026)

Temporal myopia in building Life Cycle Assessment? Granular versus coarse dynamics in climate change and grid decarbonisation - Marios Kordilas; Dejan Mumovic; Yair Schwartz; Rob Cooke; Smith Mordak; Zaid Chalabi (Building and Environment, 2026)

The impact of evolving mix on building’s life cycle environmental impacts under climate change: insights from a London office case study - Marios Kordilas; Dejan Mumovic; Yair Schwartz; Rob Cooke; Smith Mordak (The International Journal of Life Cycle Assessment, 2025)
Purpose The main aim of this study is to identify how evolutions in the electricity mix and climate change affect the LCA results of buildings regarding the multitude of environmental impacts. This is of critical importance now, and one that is likely to receive growing interest in the future. Firstly, because carbon might become a secondary environmental impact to mitigate as economies achieve decarbonisation milestones, and secondly, due to concerns around the trade-offs between the environmental impacts. Methods This study evaluates the lifecycle environmental impacts of a case study office building in London by considering climate change in the UK (using CIBSE weather files) and electricity mix evolution in the UK (using National Grid ESO data), EU (using EU commission data) and China that influence operational and embodied modules of LCA. Electrification of transport is also considered, reflecting the forementioned electricity mixes. A dynamic LCA approach was followed in which the inventory was modified to reflect future electricity mixes. The influence of climate evolution was considered through dynamic thermal simulations according to London’s future climatic projections provided by CIBSE’s weather files that were then translated into lifecycle environmental impacts through the modified inventory. Results and discussion Results of applying a dynamic approach in LCA show that there are several co-benefits of grid decarbonisation when it comes to the building’s environmental impacts. However, ecotoxicity and land occupation might come to light. Climate change led to minor reductions in the operational electricity needs, indicating that no significant savings are to be expected in the case of actively cooled buildings without free ventilative cooling. Evolving electricity mixes do not significantly reduce material embodied impacts for this case study, showing that the reduction of lifecycle impacts cannot rely only on future electricity mix evolutions. The electrification of transport was found to have an adverse effect on the building’s embodied ionising radiation impact, highlighting the importance of sourcing materials locally to avoid long transportation distances. A new type of performance gap is proposed for the building’s lifecycle environmental impacts. This can be defined as ‘the difference between the predicted and the actual environmental impact resulting from the mismatch between the actual case and the life cycle inventory’. Conclusions Future research is needed to investigate how sensitive results are to other assumptions and how improvements in material manufacturing affect the obtained results.

AVOTREX : A Global Dataset of Extinct Birds and Their Traits - Ferran Sayol; Joseph P. Wayman; Paul Dufour; Thomas E. Martin; Julian P. Hume; Maria Wagner Jørgensen; Natàlia Martínez‐Rubio; Ariadna Sanglas; Filipa C. Soares; Rob Cooke; Chase D. Mendenhall; Jay R. Margolis; et al. (Global Ecology and Biogeography, 2024)
Motivation Human activities have been reshaping the natural world for tens of thousands of years, leading to the extinction of hundreds of bird species. Past research has provided evidence of extinction selectivity towards certain groups of species, but trait information is lacking for the majority of clades, especially for prehistoric extinctions identified only through subfossil remains. This incomplete knowledge potentially obscures the structure of natural communities, undermining our ability to infer changes in biodiversity across space and time, including trends in functional and phylogenetic diversity. Biases in currently available trait data also limit our ability to identify drivers and processes of extinction. Here we present AVOTREX, an open‐access database of species traits for all birds known to have gone extinct in the last 130,000 years. This database provides detailed morphological information for 610 extinct species, along with a pipeline to build phylogenetic trees that include these extinct species. Main Types of Variables Contained For each extinct bird species, we provide information on the taxonomy, geographic location, and period of extinction. We also present data on island endemicity, flight ability, and body mass, as well as standard measurements of external (matching the AVONET database of extant birds) and skeletal morphology from museum specimens where available. To ensure comprehensive morphological data coverage, we estimate all missing morphological measurements using a data imputation technique based on machine learning. Finally, we provide an R package to graft all extinct species onto a global phylogeny of extant species (BirdTree). Spatial Location and Grain Global. Time Period and Grain All known globally extinct bird species from 130,000 years ago up until 2024. Major Taxa and Level of Measurement Birds (Class Aves), species level. Software Format Spreadsheets (.csv) stored in Dryad.

Protected areas support more species than unprotected areas in Great Britain, but lose them equally rapidly - Rob Cooke; Francesca Mancini; Robin J. Boyd; Karl L. Evans; Anna Shaw; Thomas J. Webb; Nick J.B. Isaac (Biological Conservation, 2023)

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Influence of agri-environment scheme options on territory settlement by Yellowhammer (Emberiza citronella) and Corn Bunting (Emberiza calandra) - Malcolm D. Burgess; Jenny A. Bright; Antony J. Morris; Rob H. Field; Philip V. Grice; Andrew I. Cooke; Will Peach (Journal of Ornithology, 2015)

Timing of Variscan HP-HT metamorphism in the Moldanubian Zone of the Bohemian Massif: U-Pb SHRIMP dating on multiply zoned zircons from a granulite from the Dunkelsteiner Wald Massif, Lower Austria - Gertrude Friedl; Rob A. Cooke; Friedrich Finger; Neal J. McNaughton; Ian R. Fletcher (Mineralogy and Petrology, 2011)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)